2020
DOI: 10.1038/s41398-020-01027-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental regulation of the chloride transporter KCC2: switching inflammation off to switch the GABA on?

Abstract: Chloride homeostasis, the main determinant factor for the dynamic tuning of GABAergic inhibition during development, has emerged as a key element altered in a wide variety of brain disorders. Accordingly, developmental disorders such as schizophrenia, Autism Spectrum Disorder, Down syndrome, epilepsy, and tuberous sclerosis complex (TSC) have been associated with alterations in the expression of genes codifying for either of the two cotransporters involved in the excitatory-to-inhibitory GABA switch, KCC2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 156 publications
0
34
0
Order By: Relevance
“…The molecular processes by which exercise and/or environmental enrichment increase KCC2 levels are still unknown, but endurance training is recognized to upregulate BDNF expression, which is a major determinant of KCC2 upregulation [ 105 ]. Similarly, an upregulation of insulin-like growth factor-1 (IGF-1) could decrease the ratio between the expression of NKCC1 and KCC2, promoting the developmental switch of GABA polarity from excitation to inhibition [ 106 ]. However, very few studies have assessed the direct effect of HIIT on KCC2 expression after stroke [ 38 ].…”
Section: How Can Hiit Promote Neuroplasticity and Cognitive Benefimentioning
confidence: 99%
“…The molecular processes by which exercise and/or environmental enrichment increase KCC2 levels are still unknown, but endurance training is recognized to upregulate BDNF expression, which is a major determinant of KCC2 upregulation [ 105 ]. Similarly, an upregulation of insulin-like growth factor-1 (IGF-1) could decrease the ratio between the expression of NKCC1 and KCC2, promoting the developmental switch of GABA polarity from excitation to inhibition [ 106 ]. However, very few studies have assessed the direct effect of HIIT on KCC2 expression after stroke [ 38 ].…”
Section: How Can Hiit Promote Neuroplasticity and Cognitive Benefimentioning
confidence: 99%
“…Fetal exposure to maternal stressors and enhanced allostatic load, can disrupt optimum brain development. Mapping pathologic pathways implicated as central mediators of the effects of early life stress in brain function, identified altered HPA axis responses and perturbed glucocorticoid signalling as well as various modifications in the fetal brain function, including impaired GPCR signalling, alterations in neurotransmission and disturbed functionality of neuronal circuits (21)(22)(23)(24)(25)(26). Thus, as the phenotype responds to the intrauterine environment, these adaptations can sometimes result in long term consequences and increased risk for disease in later life (27).…”
Section: Adaptation To Maternal Stress Resilience and Neurodevelopmentmentioning
confidence: 99%
“…Studies revealed that offspring born to immune-challenged mothers, exhibit altered gene expression of genes encoding the two cotransporters involved in the excitatory-to-inhibitory GABA switch, leading to an increased NKCC1:KCC2 ratio and thus experience a delay in the developmental switch of GABA signalling. This might represent a link between early life environmental hits and behavioural changes in adult life (22)(23)(24)50).…”
Section: Placental Stress Signals and Fetal Brain Neurotransmitters And Gpcrsmentioning
confidence: 99%
“…Maternal T helper 17 cells have been implicated in cortical and behavioral abnormalities in MIA offspring [30]. Also, maternal infections have been found to reduce brain offspring's potassium-chloride cotransporter 2 expression, thus delaying the excitatoryto-inhibitory GABA switch [17,18]. Nevertheless, the NVU could directly play a role: We know that SARS-CoV-2 can directly affect the brain microvascular endothelium and thus force its way to the brain parenchyma [37].…”
Section: Direct Effects Of Congenital Infections On the Nvu And The Brain Vasculaturementioning
confidence: 99%
“…Together, these findings indicate that the physiological role of cytokines and immune factors in the government of brain development is likely to be disrupted upon stress and maternal immune responses. MIA models, mostly represented by rodents exposed to Toll-like receptors' agonists (mainly lipopolysaccharide -LPS and polyinosinic:polycytidylic acid-PolyI:C) during the gestational periods to mimic an inflammatory response to a pathological agent, are crucial to shed light on the underpinning molecular mechanisms which link the maternal-prenatal stress with the increased risk of psychiatric disorders in the progeny [17,18]. Of note, MIA has proved the non-necessity of congenital infections, of which there is limited evidence for influenza virus infections [19].…”
Section: Introductionmentioning
confidence: 99%